Cooperation in R&D in the pharmaceutical industry-The network as an organizational innovation governing technological innovation - Starpoli, Carine
The paper sets out to understand the development of the networking form of partners in the pharmaceutical industry where, so far, only two companies have adopted this form of organization.
This paper aims at understanding the historical emergence of the network organizational form of partners in the pharmaceutical industry following the development of biotechnologies. Unlike the situation in other high-tech industries, the network, as a governance structure for cooperative relationships, is still marginal in this industry compared to complex but 'classical' forms of cooperation (R&D agreements, cross-licensing, joint ventures, mergers/acquisitions). Only two pharmaceutical companies have adopted such an organizational form to govern their cooperation in R&D. Referring to other industries, the network could be considered as an efficient alternative in the context of high technological uncertainties associated with biotechnologies and of industrial restructuring leading to the globalization of innovative practices and processes. After an Introduction, in Section 2 we discuss the link between technological innovation and organizational innovation to highlight the emergence of a multiplicity of institutional arrangements governing cooperation in R&D. Among all these hybrid forms, the network raises organizational issues since it short-circuits traditional strategic operations in the pharmaceutical industry. In Section 3 we define what we call a 'tight' network, referring to this particular institutional arrangement. In Section 4 we consider the empirical case of Rhone-Poulenc Rorer, and identify the main reasons which have influenced the creation of a network of partners focusing on gene therapy, Rhone-Poulenc Rorer-Gencell.
Keywords: Organizational innovation; Technological innovation